2020
DOI: 10.2147/cmar.s267415
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Association Between Smartphone Use and Breast Cancer Risk Among Taiwanese Women: A Case-Control Study</p>

Abstract: Introduction Breast cancer is a common malignancy worldwide. Smartphones have gradually become indispensable to our modern lives and have already changed lifestyles of human beings. To our best knowledge, no study has investigated the relationship between smartphone use and breast cancer. This case-control study purposely investigated the relationship between smartphone use and breast cancer risk. Materials and Methods This was a case-control study comprising 894 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It is worth noting that exposure to light at night can disrupt the secretion of melatonin and cause circadian rhythm disruption, which can increase the risk of breast cancer. A case-control study on 894 healthy controls and 211 patients with breast cancer showed that excessive smartphone use significantly increased the risk of breast cancer, particularly for participants with smartphone addiction, a close distance between the breasts and smartphone, and the habit of smartphone use before bedtime [ 131 ]. Women who work or are exposed to high levels of light at night, such as factory workers and doctors, are also at increased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that exposure to light at night can disrupt the secretion of melatonin and cause circadian rhythm disruption, which can increase the risk of breast cancer. A case-control study on 894 healthy controls and 211 patients with breast cancer showed that excessive smartphone use significantly increased the risk of breast cancer, particularly for participants with smartphone addiction, a close distance between the breasts and smartphone, and the habit of smartphone use before bedtime [ 131 ]. Women who work or are exposed to high levels of light at night, such as factory workers and doctors, are also at increased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This letter is regarding our concerns regarding the paper entitled "The Association between Smartphone Use and Breast Cancer Risk among Taiwanese Women: A Case-Control Study" by Shih et al, published in Cancer Management and Research. 1 Although this paper addresses a very important topic, it has some shortcomings that at least to some extent, affect its conclusion. In their casecontrol study on 894 healthy controls and 211 patients with breast cancer, the authors had asked the participants to provide information on their sleep quality, smartphone addiction, and smartphone use.…”
Section: Dear Editormentioning
confidence: 96%
“…Hiatt and Beyeler (2022) show that climate change will affect women's cancers through various mechanisms, including the effects of air pollution, ultraviolet radiation (UV), environmental toxins, or aberrant food supplies [88]. Shih et al (2020) sustained that even smartphone long-term use significantly increases the BC risk, due to a close distance between breasts and smartphone, and the habit of smartphone use before bedtime and night [89]. Also, night shift work, exposure to light at night, and circadian disruption may increase the BC risk [90].…”
Section: Bc Is An Ecological/environmental Disordermentioning
confidence: 99%